2016
DOI: 10.4038/sljm.v24i2.8
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of rate and factors affecting malignant transformation of oral submucous fibrosis in patients attending the Oral Medicine Clinic, Dental Hospital Peradeniya, Sri Lanka - A retrospective study

Abstract: Background: Oral submucous fibrosis (OSF) is a chronic, progressive, scarring and potentially malignant disease of the oral mucosa seen primarily in the Indian subcontinent and in South East Asia. OSF is a premalignant condition with a malignant transformation rate varying from 7-12%. Even though OSF and oral cancer are common in Sri Lanka, malignant transformation potential and rate have not been studied in our population. Objectives: To identify the relationship of malignant transformation with age, gender, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 11 publications
(21 reference statements)
3
14
3
Order By: Relevance
“…The studies included in this review were conducted in three different countries(India, Taiwan and Sri Lanka). Four studies have actually surveyed the population and followed them up 10,11,13,18 . Five studies obtained retrospective data of patients from the records and followed them up, 11,14–16,18 whilst one study reported information from records only 13 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in this review were conducted in three different countries(India, Taiwan and Sri Lanka). Four studies have actually surveyed the population and followed them up 10,11,13,18 . Five studies obtained retrospective data of patients from the records and followed them up, 11,14–16,18 whilst one study reported information from records only 13 …”
Section: Resultsmentioning
confidence: 99%
“…Except for the two studies 11,12 where information was not provided, five studies reported malignant transformation to be more amongst males as compared to females 13–17 . The male to female ratio of 5:3 was mentioned in one study only 18 . The etiological factor as betel quid with tobacco was reported in two studies 10,15 whilst two other studies mentioned betel quid chewing habit along with alcohol consumption and/or smoking 17 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease is witnessed in countries where the habit of betel chewing is recurrently practiced. The rate of malignant transformation is 7-13 % (Jayasinghe et al, 2016). Albeit the available epidemiological evidence implies that the chewing of areca nut is a definitive risk factor for progress of OSMF, imperceptibly chewers procure the disease and it is not a dose-response related disease.…”
Section: Introductionmentioning
confidence: 99%